Smicridea (Trichoptera, Hydropsychidae) from 3 Brazilian Amazonian States: New species, larval taxonomy and bionomics - Albino, Jeyson Lazaro Duque; Pes, Ana Maria; Hamada, Neusa (Zootaxa, 2011)
Seven new species of Smicridea (Rhyacophylax) are described from the states of Amazonas, Roraima and Mato Grosso, Brazil: S. araguaiense sp. nov., S. bicornuta sp. nov., S. bifasciata sp. nov, S. dentisserrata sp. nov., S. helenae sp. nov., S. flinti sp. nov., S. roraimense sp. nov. Larvae and pupae of S. helenae sp. nov., S. (Smicridea) palifera Flint, S. (S.) obliqua Flint and S. (R.) appendiculata Flint are described and illustrated. Morphological variation observed in S. (R.) coronata Flint and S. appendiculata is presented. Species bionomics are presented and new species are recorded for Brazil and for the states of Amazonas, Roraima and Mato Grosso.